REFORMULATING GENDER NORMS IN SAUDI ARABIA: CULTURAL LIBERALIZATION UNDER VISION 2030 - Fakih Fadilah Muttaqin; Yazid Hady; Nofi Maria Krisnawati; Endang Susanti; Siti Rohwati (Center for Gender and Child Studies (Pusat Studi Gender dan Anak) LP2M UIN Syarif Hidayatullah Jakarta, 2025)
Abstract. This article examines the process of gender norm reconstruction in Saudi Arabia within the framework of Vision 2030, focusing on the state's strategy of selectively liberalizing culture to support its authoritarian modernization project. In the conservative Wahhabi tradition, women's positions have been limited by legal, social, and religious structures. However, since 2016, under the leadership of Crown Prince Mohammed bin Salman, the Saudi government has initiated a series of reforms that have allowed women to drive, work in the public sector, and access entertainment and cultural spaces. This article uses a qualitative-analytical approach with an exploratory-descriptive design through discourse and policy analysis, as well as a theoretical framework of modernization, state feminism, and ideological control in authoritarian states. It was found that gender reforms in Vision 2030 are not merely a form of emancipation, but rather a state strategy to build new legitimacy, attract global investment, and reframe national identity without overhauling the authoritarian political order. This study makes an important contribution to understanding the dynamics of gender in contemporary Muslim societies and development politics in the Gulf region. Abstrak. Artikel ini mengkaji proses rekonstruksi norma gender di Arab Saudi dalam kerangka Visi 2030, dengan fokus pada strategi negara dalam meliberalisasi budaya secara selektif untuk menopang proyek modernisasi otoriter. Dalam tradisi Wahhabisme yang konservatif, posisi perempuan selama ini dibatasi oleh struktur hukum, sosial, dan religius. Namun sejak 2016, di bawah kepemimpinan Putra Mahkota Mohammed bin Salman, pemerintah Saudi menginisiasi serangkaian reformasi yang mengizinkan perempuan untuk mengemudi, bekerja di sektor publik, serta mengakses ruang hiburan dan budaya. Artikel ini menggunakan pendekatan kualitatif-analitis dengan desain eksploratif-deskriptif melalui analisis wacana dan kebijakan, serta kerangka teori modernisasi, feminisme negara, dan kontrol ideologis dalam negara otoriter. Ditemukan bahwa reformasi gender dalam Visi 2030 bukan semata bentuk emansipasi, melainkan strategi negara untuk membangun legitimasi baru, menarik investasi global, dan membingkai ulang identitas nasional tanpa merombak tatanan politik yang otoriter. Kajian ini memberikan kontribusi penting dalam memahami dinamika gender di masyarakat Muslim kontemporer dan politik pembangunan di kawasan Teluk.